Strategi Guru PAI dalam Pembinaan Akhlak Mulia Generasi Alpha (Studi pada Sekolah Dasar Kota Sabang) - Ardiansyah, Ardiansyah; Saiful, Saiful; Fikri, Mumtazul (FITRAH: International Islamic Education Journal, 2024)
The Alpha Generation, born in the digital era, presents significant challenges in shaping noble character, especially amidst the influence of technology and social media. This study aims to explore the strategies, challenges, and solutions in fostering noble character in the Alpha Generation by Islamic Religious Education (PAI) teachers at elementary schools in Sabang City. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The study found that PAI teachers implement an integrative strategy, combining religious and moral values into the learning process. Methods employed include role modeling, lectures, discussions, and religious activities such as congregational prayers and Quranic studies. Teachers also encourage student participation in extracurricular activities focused on character development, aiming to internalize noble character in students’ daily lives. The primary challenges faced include the negative influence of technology and social media, which often expose students to content that conflicts with moral values. Additionally, a lack of active student involvement in character-building activities and differences in parenting styles at home further hinder consistent application of moral values. To address these challenges, PAI teachers enhance collaboration with parents to ensure that character development aligns between school and home. Technology is also leveraged to provide positive content through educational platforms. Teachers regularly evaluate students' character development through reflective activities. This holistic approach effectively reduces obstacles and strengthens students’ character amidst the wave of digitalization.   Abstrak Generasi Alpha yang lahir di era digital menghadirkan tantangan besar dalam pembentukan akhlak mulia, terutama di tengah pengaruh teknologi dan media sosial. Penelitian ini bertujuan untuk mengetahui strategi, tantangan, dan cara mengatasi kendala dalam pembinaan akhlak mulia generasi Alpha oleh guru PAI di Sekolah Dasar Kota Sabang. Menggunakan metode kualitatif deskriptif, data diperoleh melalui wawancara dan Observasi. Hasil penelitian menunjukkan bahwa guru PAI menerapkan strategi integratif, menggabungkan nilai-nilai agama dan moral dalam pembelajaran. Metode yang digunakan meliputi keteladanan, ceramah, diskusi, serta kegiatan keagamaan seperti shalat berjamaah dan pengajian. Guru juga mendorong partisipasi siswa dalam kegiatan ekstrakurikuler berbasis pengembangan karakter, bertujuan menginternalisasi akhlak mulia dalam kehidupan sehari-hari. Tantangan utama yang dihadapi adalah pengaruh negatif teknologi dan media sosial, yang sering kali menyajikan konten bertentangan dengan nilai-nilai moral. Selain itu, kurangnya keterlibatan siswa dalam kegiatan pembinaan akhlak serta perbedaan pola asuh di rumah turut menjadi penghambat. Hal ini menyulitkan penerapan nilai-nilai akhlak secara konsisten.  Untuk mengatasi tantangan tersebut, guru PAI meningkatkan kolaborasi dengan orang tua agar pembinaan akhlak dapat berjalan selaras antara sekolah dan rumah. Teknologi juga dimanfaatkan untuk menyediakan konten positif melalui platform edukatif. Guru secara berkala mengevaluasi perkembangan akhlak siswa melalui kegiatan refleksi bersama. Pendekatan holistik ini efektif dalam mengurangi kendala dan memperkuat karakter siswa di tengah arus digitalisasi.